A Framework for Incorporating the “Learning How to Learn” Approach in Teaching STEM Education - Othman Abu Khurma; Abdulla Al Darayseh; Yahia Alramamneh (Education Sciences, 2022)
The importance of STEM subjects for the purposes of scientific and technological development has gained global momentum. Yet, there are various obstacles to applying a STEM education in the context of preparing students for a scientifically and technologically advanced society. There has been little research on how engineering can be incorporated into the elementary school curriculum. This study, thus, provides a systematic review of the learning techniques and structured framework that are used to support learning in the fields of science, technology, engineering, and mathematics (STEM). It also aids in identifying students’ shifts in interest toward STEM subjects, as well as their desire to pursue future STEM-based careers. This study makes use of a systematic literature review of high-impact journals with a Q1 or Q2 ranking. It was also found that there are hurdles in regard to the teaching approach that is used for STEM subjects. This suggests that there are numerous opportunities that can be exploited by educators in their hunt for a better STEM teaching approach. Finally, researchers must create features that enable students to gain fundamental competencies within the STEM disciplines. Future applications must include the experimental support for the purposes of inquiry-based learning activities.